Variation in Total Dissolved Iron Output and Iron Species During Extreme Rainfall Events. Issue 6 (15th February 2016) - Guan, Jiunian; Yan, Baixing; Wang, Lixia; Zhu, Hui; Cheng, Long
Abstract : Due to climate changes, the occurrence of extreme rainfall events (EREs) has been increasing worldwide and is expected to affect the output of total dissolved iron (TDFe) significantly. EREs occurred in the Songhua River Basin in 2013. To study the effects of EREs on the TDFe output and iron species, water samples were collected to analyze both TDFe concentration and the water quality. Filtration and ultrafiltration methods were employed to analyze the iron speciation according to the molecular weights of the TDFe species. The results showed that the TDFe concentration ranged from 0.46 to 1.10 mg/L (0.69 mg/L on average), and was increased significantly compared with that observed during the regular flood seasons from 2008 to 2012. The TDFe output reached 3.59 × 10 4 tons during EREs, almost equal to the annual output level in the Songhua River. Species analysis indicated that complexed iron at a low‐molecular‐weight was the dominant species during the EREs. The impulse of the TDFe output can be attributed to a hydrological connection to riparian wetlands and iron‐rich terrestrial runoff, and it may exert an influence on the water quality and alter the transport and cycling of other chemicals (e.g., trace elements, nitrogen, and phosphate) in the Songhua River. Abstract : During the 2013 extreme rainfall events, both concentration and output of total dissolved iron in the Songhua River increased significantly, which can be attributed to the hydrological connection to riparian wetlands and territorial runoff. Meanwhile, instead of Fe(II), complexed iron at a low molecular weight became the dominant species. These alterations may influence the water quality and chemical cycling in the river.